(untitled) (Ustozlar uchun, 2025)
This study investigates the challenges faced by learners of English as a Second Language (L2) in mastering vowel pronunciation, focusing on the effects of native language (L1) interference and pedagogical factors. English vowels are complex due to variations in length, tension, and quality, which often cause confusion among learners whose L1 has fewer or structurally different vowel sounds. Using a qualitative descriptive approach, the study analyzes international and Uzbek research to identify common pronunciation difficulties, cross-linguistic influences, and effective instructional methods. Findings reveal that vowels such as /ɪ/, /æ/, /ʊ/, and /ə/ are among the most problematic for learners across linguistic backgrounds, while R-colored vowels and the schwa sound also pose significant challenges. The study highlights the importance of explicit pronunciation instruction, contrastive analysis between L1 and English vowel systems, and the use of technology-assisted pronunciation tools. It concludes that developing phonetic awareness and integrating innovative, practice-oriented methods can greatly improve learners’ vowel pronunciation and overall communicative competence in English.